Pragmatic analysis of solar photovoltaic system design in an institutional building in eastern India - Sharma, Renu; Goel, Sonali; Lenka, Saumya Ranjan (Frontiers in Energy Research, 2023)
PV systems connected to the grid are primarily designed to generate clean energy to fulfil the rising energy demand. To predict the performance and efficacy of PV systems, several installation aspects are employed, such as location, local meteorological data, orientation, optimal tilt angle, varying losses, and energy yield estimation. Siksha 'O' Anusandhan Deemed to be University, Bhubaneswar (Latitude 20.24° N and Longitude 80.85° E) has taken one such initiative by installing a 13 kWp rooftop grid-connected solar photovoltaic system in one of its institutional buildings. The solar PV system is fixed at an angle of 21° and is installed on the rooftop of a 25-meter height building. From the result, the annual electricity supplied to the grid is 17.79 MWh, final yield of 3.80 h/d, reference yield of 4.62 h/d and performance ratio of 0.82. The solar PV system installed at the institution is predicted to have reduced 17443.02 kg of CO2, 22.07 kg of SO2, and 46.1 kg of NOx from the atmosphere per year. The lebelised cost of energy (LCOE) of the installed PV system is 9.408 INR/kWh with a payback of 9.8 years. This study provides the techno-economic feasibility of installing grid-connected solar PV systems on the roof of an institutional building and help the solar installers in establishing the most efficient solar photovoltaic system’s sizing and design.